(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2023)
Digital technologies have changed society and continue to influence almost all business functions and industries. Governments and businesses across all forms of ownership are increasingly relying on digital technologies to capture and use data for financial and other purposes. Companies are developing strategies to digitize their business operations, especially in the accounting department. Accounting is a complex, multifaceted process that involves many single-entry operations, multiple repetition of the same computational actions, as well as preparation of various documents and reports. The use of information technology makes it possible to replace manual work with automated work, while using the work of accountants more as analysts and controllers. The use of "cloud" technologies in accounting is quite effective. With the help of "cloud" technologies, all tasks of traditional accounting can be performed, namely, financial, management, and tax accounting, and tax accounting, as well as to prepare statistical reports, generate primary accounting documentation, and calculate taxes. Digital technologies facilitate environmental innovations that contribute to sustainable development by reducing environmental impacts and optimizing resource utilization. As these technologies evolve and converge with biotechnology and natural science, they can generate extraordinary innovations that will contribute to a sustainable future. Disclosure of environmental accounting information is key to reporting. In particular, the obligation to report to stakeholders (e.g., consumers, business partners, investors, employees) when using the resources of the current environment raises the status of the company to a higher level of mutual trust in society.